Standpoint semantics for polysemy in spatial prepositions. (11th January 2020) - Rodrigues, Edilson J; Santos, Paulo E; Lopes, Marcos; Bennett, Brandon; Oppenheimer, Paul E
Abstract: In this paper, we present a formalism for handling polysemy in spatial expressions based on supervaluation semantics called standpoint semantics for polysemy (SSP). The goal of this formalism is, given a prepositional phrase, to define its possible spatial interpretations. For this, we propose to characterize spatial prepositions by means of a triplet image schema, semantic feature, spatial axis . The core of SSP is predicate grounding theories, which are formulas of a first-order language that define a spatial preposition through the semantic features of its trajector and landmark. Precisifications are also established, which are a set of formulae of a qualitative spatial reasoning formalism that aims to provide the spatial characterization of the trajector with respect to the landmark. In addition to the theoretical model, we also present results of a computational implementation of SSP for the preposition 'in'.